THE IMPORTANCE OF DEMAND MANAGEMENT IN COMPETITIVE ENERGY MARKETS: Analysing how it can be used and effectively implemented to improve energy efficiency and load management - Appadoo, Rushvin (2007)
When operating a domestic appliance, say a cooling fan, its rotations need to be in harmony with those of the massive generating turbines in the many power stations; however, the level of technical complexity behind this harmony is simply unimaginable (Bunn, 2004). Yet, technical complexity is no more the sole intricacy plaguing the energy industry. Liberalization of electricity markets, coupled with pressure to meet the Kyoto Protocol's environmental requirements, have further added to this complexity. These factors have brought to the fore front the importance of demand management initiatives. In this paper, it has been analysed how these initiatives, which take the form of energy efficiency measures and load management measures, can be implemented.